Investigating The Approaches of English Teachers in Fostering EFL Students’ Language proficiency - Anita Anggraeni; Cynantia Rachmijati (Al-Lisan: Jurnal Bahasa, 2020)
This research is qualitatively descriptive, intending to define the efforts of English teachers at Boarding school and hereinafter referred to as Pesantren (al-Fatah) to develop students’ English language proficiency. Subjects of this study are two English teachers and Students at Pesantren al-Falah. This study also investigates the way of English teaching methods or strategies in the classroom. There are two main instruments to collect data, those are Observation and interview guidelines. The result of the study indicates that the most teaching methods used are still a teacher-centered, direct method and habituation. This is due to the influence of the traditional Arabic learning model which is still largely focused on what is conveyed by the teacher in the classroom. But this Pesantren also implemented a communicative approach to develop the speaking skill of the students. One of the challenges faced is students' negative perceptions of English which assume that English is a western culture that is synonymous with negative things. Therefore, to further strengthen the development of English language skills, English teachers need to be more exposed to English by offering their students even more usual practice and the right media and literature to minimize negative perceptions of Western culture.